2020
DOI: 10.1021/acs.biomac.0c00057
|View full text |Cite
|
Sign up to set email alerts
|

Lignin-Based Epoxy Resins: Unravelling the Relationship between Structure and Material Properties

Abstract: Here we investigate the relationship between thermomechanical properties and chemical structure of well-characterized lignin-based epoxy resins. For this purpose, technical lignins from eucalyptus and spruce, obtained from the Kraft process, were used. The choice of lignins was based on the expected differences in molecular structure. The lignins were then refined by solvent fractionation, and three fractions with comparable molecular weights were selected to reduce effects of molar mass on the properties of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
101
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 145 publications
(124 citation statements)
references
References 51 publications
5
101
0
3
Order By: Relevance
“…In addition, the average numbers of epoxy groups (truen ) in each macromolecule [epoxy content (mol g −1 )× M n ] are given in Table 2. The reactivities of hydroxy (OH) functional groups in lignin toward ECH, in decreasing order, are phenolic‐OH>carboxylic acid>aliphatic‐OH [30] . It has been reported that the phenol epoxidation mechanism has three steps [51] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the average numbers of epoxy groups (truen ) in each macromolecule [epoxy content (mol g −1 )× M n ] are given in Table 2. The reactivities of hydroxy (OH) functional groups in lignin toward ECH, in decreasing order, are phenolic‐OH>carboxylic acid>aliphatic‐OH [30] . It has been reported that the phenol epoxidation mechanism has three steps [51] .…”
Section: Resultsmentioning
confidence: 99%
“…These attributes cause lignin to have lower reactivity toward ECH than BPA and possibly result in resin with lower homogeneity. Lignin can be incorporated into epoxy resin via three different methods: 1) blending with petroleum‐based epoxy resin, [24,25] 2) modification of lignin followed by epoxidation, [23,26–30] and 3) epoxidation of unmodified lignin [16,31,32] . Although many studies have focused on utilizing lignin in epoxy resin, [23,27,33,34] they mostly used modified lignin (fractionated or lignin monomers) [23,27,29] .…”
Section: Introductionmentioning
confidence: 99%
“…The lignin fraction could be used directly as a polymer precursor for material synthesis or catalytically depolymerized to platform monomers. Based on their functionality, structure, low DP n and demonstrably narrow Đ , these lignins might be suitable as polymer precursors for the synthesis of thermosetting resins, as shown in recent studies . In those cited studies, oligomeric fractions were shown to be preferable to polymeric fractions for the synthesis of homogeneous materials, due to their mutual solubility with other chemical components used in the synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…They may occur in the form of powder, microparticles or nanoparticles, or long and short fibers [2][3][4]. The use of such modifiers as biochar [5][6][7], carbon nanotubes [8][9][10], basalt powder [11][12][13][14], lignin [15,16], and ground waste from the agricultural [17][18][19] and food industries [20][21][22] in polymer composites has been the subject of many scientific papers in recent years. A significant change in the properties of the polymer matrix is obtained by using additives of various shapes in the form of particles and fibers.…”
Section: Introductionmentioning
confidence: 99%